A global perspective on the governance-health nexus - Mohammad Naim Azimi; Mohammad Mafizur Rahman; Son Nghiem (BMC, 2023)
Abstract Background This study raises two key arguments: First, government health expenditure (GHE) and per capita out-of-pocket expenditures on healthcare (OPEH) are sensitive to contemporary good governance practices, giving policy importance to the exogeneity of healthcare determinants, i.e., governance for health rather than health governance. Second, it is the income level of countries that reflects the volatility of the governance spillovers on the subject. Methods The present study constructs a composite governance index (CGI) and employs a set of panel data for 144 countries over the period from 2002 to 2020. To allow comparability and extract specific policy implications, the countries are classified as full, high-, middle-, and low-income panels. Meanwhile to﻿ delve into the short- and long-run effects of CGI on GHE and OPEH, the study employs the cross-sectionally augmented autoregressive distributed lags (CS-ARDL) model. Further, to establish a causal link between the variables, it uses the Dumitrescu-Hurlin panel causality technique. Results The results indicate that CGI is significantly cointegrated with GHE and OPEH in all recipient panels. It indicates that while CGI has significantly positive impacts on GHE and OPEH, its effects vary according to the income level of the underlying economies. The findings support the idea of governance for health and show that CGI drives the stabilization and enhancement of GHE and OPEH in the long run. Furthermore, the findings reveal that economic growth, the age dependency ratio, and tax revenue have positive effects, while the crude death rate and the child mortality rate exert negative impacts on the subject. Finally, the results highlight a unidirectional causality running from CGI to GHE and OPEH, while no feedback response is evident. Conclusions Although an increase in GHE and OPEH is associated with the improvement of the population's healthcare, the results suggest the recognition of the importance and institutionalization of good governance to streamline this improvement through effective channelization, outreach, and social environment development for extensive health inclusion.